Analisis Senyawa Kafein pada Bubuk Kopi Jenis Arabika di Kota Takengon Menggunakan Analisis Kualitatif dan Kuatitatif: Analysis of Caffeine Compounds in Arabica Ground Coffee in Takengon City Using Qualitative and Quantitative Analysis - Ernoviya Ernoviya; Afriadi Afriadi; Hesti Nadila Silfania (JURNAL FARMASI DAN MAKANAN, 2023)
Background:Coffee is a type of plant that contains caffeine and can be made into a delicious drink. Currently, coffee is the world's most popular drink after water and tea. The stuay aimed was to determine the caffeine content in Arabica ground coffee circulating in the Takengon market according to Indonesian national standards (SNI 01-7152-2006).This research was experimental by taking samples purposively. The research method used was phytochemical screening, qualitative analysis, and ultraviolet spectrophotometry at a wavelength of 273nm. The specified validation parameters were precision, linearity, LOD and LOQ.The results of the phytochemical screening of sample A in the Meyer test treatment obtained negative results but the others were positive. And in sample B, all tests were positive. In the three qualitative analyses tests on samples A and B, the results were positive. The average yield of quantitative analysis in sample A was 11.632 mg once and the daily concentration was 34.897mg. while in sample B the level was 6.663 mg once and drank 19.989mg per day. Validation test results obtained linearity r2 = 0.998, LOD and LOQ namely 0.882Âµg/ml and 2.94Âµg/ml, RSD value of 1.11%.Based on the conclusion, sample A and sample B met the requirements according to SNI 2006 (50mg once and 150mg daily) and also met the requirements according to the Pharmacopoeia Edition III, namely a maximum dose of 500 mg once and 1.5g daily to future researchers to determine levels other than caffeine found in Arabica coffee in Takengon.